Validity of direct sputum smear microsocpy (DSSM) in diagnosing PTB among prisoners and jail guards Bayesian approach - Rosales, Ma. Grace C. (2017)
Tuberculosis (TB) is one of the major public health concerns in the country. Although the Philippines already achieved the MDGs in 2012, Filipino?s should not be complacent. TB is a bacterial disease that can easily spread and until now, TB has not been fully eradicated especially among the high risk populations like the prisoners. It is therefore important that early and accurate diagnosis and prompt treatment of TB be done. This study aimed to evaluate using Bayesian approach the validity of direct sputum smear method (DSSM) in comparison with culture isolation of mycobacteria in LJ medium in the diagnosis of TB. This study utilized data derived from indivuduals of the study of TB in prisons with both DSSM and culture results. Bayesian estimation of the different measures of validity was performed and compared with the outcome of the frequentist approach. A total of 1171 participants with both the sputum and culture results were included, 67 (5.7%)were culture proven positive for TB. Through application of the Bayesian approach with uniform prior distribution, it was shown that the sensitivity and specificity of DSSM in detecting Mycobacterium tuberculosis were 50.7% (95% CI: 39.2% - 62.5%) and 98.3% (97.5% - 99.0%), respectively. The PPV was 64.5% (95% CI: 51.3% - 76.5%) and the NPV was 97.0% (95% CI: 96.0% - 97.9%) while the LR+ was 31.1 (95% CI: 18.4 ? 50.7) and the LR- was 0.50 (95% CI:0.38 ? 0.62). On the other hand, use of the prior information from three (3) previous studies done among prisoners yielded more precise estimates of the different measures of validity. The sensitivity and specificity were 53.1% (95% CI: 44.0% - 62.1%) and 98.1% (95% CI: 97.3% - 98.8%) respectively. The PPV was 72.8% (95% CI: - 63.0% - 81.8%) and the NPV was 95.7% (95% CI: 94.6% - 96.6%). The LR+ was 29.8 (95% CI: 18.64 ? 46.75) and the LR- was 0.48 (95% CI: 0.39 ? 0.57). This shows that the use of prior information inherent in the Bayesisn approach gives more precise estimates of the different measures of validity of a diagnostic test.
Available in CD, pdf copy.
Thesis (Master of Science in Public Health (Biostatistics)--University of the Philippines Manila
Keywords: Tuberculosis; Tuberculosis -- Diagnosis